Surveillance of antimicrobial resistance and evolving microbial populations in Vermont: 2011-2018. Issue 10 (2nd October 2020) - Stelling, John; Read, Jennifer S.; Fritch, William; O'Brien, Thomas F.; Peters, Rob; Clark, Adam; Bokhari, Marissa; Lion, Mattia; Katwa, Parisha; Kelso, Patsy
ABSTRACT: Objective: This study presents trends in organism isolation and antimicrobial resistance in routine microbiology test results from acute-care hospital microbiology laboratories in Vermont. Methods: Organism identifications and antimicrobial susceptibility test results were captured from acute-care hospital laboratories to monitor geographic and temporal trends in resistance and emerging microbial threats with the free WHONET software. Results: Data were provided from 12 acute care hospital laboratories from 2011 through 2018 for 318, 833 isolates from 148, 994 patients (70% female, 74% outpatient, and 63% urine). Significant differences (p < 0.05) in age, gender, and antimicrobial susceptibility results (e.g. Escherichia coli and levofloxacin) between outpatient and inpatient isolates were identified with temporal increases in certain species (e.g. Aerococcus urinae ) and resistance (e.g. Streptococcus pneumoniae and erythromycin). The use of multi-resistance phenotypes demonstrated significant heterogeneity (p < 0.05) in MRSA strains between facilities, for example Staphylococcus aureus resistant to six priority antimicrobials were found in no critical access hospitals (fewer than 25 inpatient beds) but in all non-critical access hospitals. Conclusions: Comprehensive electronic surveillance of antimicrobial resistance utilizing routine clinical microbiology data with free software tools offers early recognition and tracking of emerging community and healthcare resistance threats at the local and state level.